Optimizing Extraction, Evaluating Antioxidant Activity, and Analyzing Bioactive Compounds in Trikaysornmas Formula - Suphatson Limsakul; Orawan Monthakantirat; Yaowared Chulikhit; Juthamart Maneenet; Charinya Khamphukdee; Yutthana Chotritthirong; Achiraya Phasomsap; Chantana Boonyarat; Supawadee Daodee (Hindawi Limited, 2024)
The Trikaysornmas formula (TKM) represents a prevalent Thai traditional remedy utilized extensively in Thailand. Its traditional uses include appetite enhancement, functions as a nourishing tonic, and exhibits adaptogenic properties. Comprising Aegle marmelos fruit, Nelumbo nucifera stamen, and Jatropha multifida bark, this formula embodies the synergy among these three herbs. The objective of this study was to optimize the extraction method, determine the active compounds in the TKM, and evaluate its antioxidant activity. The optimization of the extraction method for this formula was studied using an experimental design. Phytochemical components such as total phenolics, total flavonoids, total carotenoids, and total alkaloids were assessed utilizing a colorimetric method. Antioxidant activities were assessed through DPPH free radical scavenging, ABTS radical cation decolorization, oxygen radical absorbance capacity, ferric reducing antioxidant power, metal chelating activity, and lipid peroxidation assay. For the analysis of active constituents in the formula, gallic acid, kaempferol-3-o-glucoside, imperatorin, vitexin, and scopoletin, a validated reversed-phase column high-performance liquid chromatography (HPLC) method was developed. The total active contents including phenolic, flavonoid, carotenoid, and alkaloid compounds were found in the formula. The developed HPLC method exhibited reliable results in all validation parameters. TKM demonstrated antioxidant activity in the models used in this research. The findings from this study can serve as valuable tools for standardization and quality control measures. Additionally, they can contribute to maximizing the possibilities inherent in this traditional Thai formulation.